Characterization of mutant histidine-containing proteins of the phosphoenolpyruvate:sugar phosphotransferase system of Escherichia coli and Salmonella typhimurium. - Waygood, E B (1987)
Histidine-containing phosphocarrier protein (HPr) is common to all of the phosphoenolpyruvate:sugar phosphotransferase systems (PTS) in Escherichia coli and Salmonella typhimurium, except the fructose-specific PTS. Strains which lack HPr activity (ptsH) have been characterized in the past, and it has proved difficult to delineate between tight and leaky mutants. In this study four different parameters of ptsH strains were measured: in vitro sugar phosphorylation activity of the mutant HPr; detection of 32P-labeled P-HPr; ability of monoclonal antibodies to bind mutant HPr; and sensitivity of ptsH strains to fosfomycin. Tight ptsH strains could be defined; they were fosfomycin resistant and produced no HPr protein or completely inactive mutant HPr. All leaky ptsH strains were fosfomycin sensitive, usually produced normal amounts of mutant HPr protein, and had low but measurable activity, and HPr was detectable as a phosphoprotein. This indicates that the regulatory functions of the PTS require a very low level of HPr activity (about 1%). The antibodies used to detect mutant HPr in crude extracts were two monoclonal immunoglobulin G antibodies Jel42 and Jel44. Both antibodies, which have different pIs, inhibited PTS sugar phosphorylation assays, but the antibody-HPr complex could still be phosphorylated by enzyme I. Preliminary evidence suggests that the antibodies bind to two different epitopes which are in part located in a beta-sheet structure.